Gastropod Species Diversity in The Mangrove Bale Area of Poton Bako East Lombok - Adam Restu; Raudatul Jannah; Rizal Umami (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Gastropoda is a class with the biggest number of species, since a class of Mollusca phylum is generally effectively adjusted to different sorts of marine and freshwater territories to earthbound conditions. So a study was conducted on the diversity of Gastropoda species in the Bale Mangrove Poton Bako East Lombok area with the aim of knowing the types of gastropods that exist in the area. The method used in this study is the quadrat transect method. The results of research on the diversity of gastropod species in the Bale Mangrove Poton Bako East Lombok area found 6 species of Gastropoda including Cerithidea sp, Telebralia sulcata, Nerita undata, Telescopium telescopium, Chicoreus capucinus, Indothais gradate. The average diversity index value of the three stations is H′ = 1.41262991 which means that the diversity of Gastropods in the Bale Mangrove Poton Bako Area of East Lombok is moderate diversity.